ANALISIS BIAYA PRODUKSI HASIL KERAJINAN ROTAN PADA INDUSTRI USAHA KECIL DAN MENENGAH (UKM) DI KECAMATAN RUMBAI, PEKANBARU (STUDI KASUS UD. DONA ROTAN FURNITURE) - Ita Yulia; Evi Sribudiani; Defri Yoza (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Rattan is one of comodity timber forest product are used as raw material for the rattan industry. Now, the development of Indonesia rattan has experienced a business decline in industrial businesses including rattan in Rumbai district. A decrease in the availability of raw materials and human resources will directly affect to cost of production. It is necessary to do a case study on the analysis of the cost of production in UD. Dona Rotan Furniture. The purpose of this resources are to know about the tpe and source of raw materials, the types of refined products produced and feasibility through the production cost analysis. The result showed that the type of raw materials used are rattan manau (Calamus manau), rattan getah (Daemonorops angustifolida Mart), rattan dahanan (Korthalsia flagelaris Miq), rattan sega (Calamus caesius) and filtrit of sega’s type. Rattan manau devired from West Sumatera, while the others are devired from Gatherers around Riau area, Jambi and South Sumatera. The amount of refined product are 26 types. Minimalist guest chairs are the most expensive type at the price Rp4.000.000,00/set, while the lowest selling price is the panda hat that Rp10.000,00. Analysis R/C ratio indicates that the industri economically viable with point 1,171 and BEP point’industry is Rp409.028.120,00. Keywords: rattan, rattan industry, cost production, R/C ratio, break even    point.